조건불리지역 밭직접지불제의 전개와 과제 - 시나가와 마사루 (한국농촌경제연구원, 2008)
The direct payment program to Less Favored Areas(LFAs) was examined in the latter half of 1990's, and it was enforced in its entirety from 2006 in Korea. This paper examines the situations of LFAs agriculture based on case study of two regions, and clarifies the evaluation and the problem of the program. The program aimed two purposes - the income assistance and activation of the LFAs. However, the effect is relatively scarce in the point of the income assistance. On the other hand, a significant result is able to be seen by using the grant for various joint activities in the point of the activation of the region. A contradiction arises between the reality and the system because a part of rented lands doesn't become the object of a grant by Agricultural Land Law.
Keywords: 조건불리지역; 직접지불제도; 지역정책; 밭농업; LFA=less favoured area; direct payment program; regional policy; upland farming